(3GdJjSjQ aj GdbQGAGJ GdSHYs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s ((3eMeO Hf YHO Gdegjef Hf YHO Gddg Hf Ybjd s)
(3ChdgG (B:s
(3CeG HYO aCfJe SCdJehfi CMSf Gddg GQTGOce Gf GUfa dce cJGHkG eNJUQkG ai ePGgH GdbQGA GdSHYI HGdGeUGQ djbQH Ydjce JfGhdg s
(3BNQgG (B:s
(3hGSbWJ Gda GdhUd ai Ghd GSe Gddg YR hLd ai LejY Pdc GSJZfGA YfgG aGYde Pdc ehabkG dWQjb GdMb hefgGL GdUhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdCdaGX HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs